Ultrasound in palliative medicine - Jakubów, Piotr (Medycyna Paliatywna/Palliative Medicine, 2015)
The ultrasound is now widely used in rapid noninvasive medical diagnostics. Progress forces palliative medicine physicians, learning techniques and possibilities ultrasound. Bedside ultrasound application increases both patient comfort and the attending doctor gravely ill. The paper presents possible to use proceedings and makes proposals FASP algorithm dedicated to hospice care in home and ambulatory services.